Microstructure Contributions to Vibrational Damping and Identification of Damage Mechanisms in Arundo Donax L: Reed Cane for Woodwind Instruments. (20th February 2017) - Kemp, Connor; Scavone, Gary
ABSTRACT: Natural cane reeds (Latin name Arundo Donax L and here termed ADL) have been used on woodwind instruments for centuries with little change. The reed acts as a mechanical valve controlling the energy input into the musical instrument and it is the musician's first option for altering the instrument's sound and response characteristics. Despite this, their consistency, variable performance, durability and sensitivity to ambient conditions make it difficult for the musician to find and maintain a reed that responds to their liking. Thus it is desirable to examine the material, microstructural and anatomical properties of the reed and their contributions to vibrational performance with input from mechanical engineers, materials scientists and musicians. The current study is part of an on-going research project, and this paper presents preliminary results. In the present work raw samples of ADL obtained from a manufacturer in pre-cut form are sectioned into longitudinal and transverse specimens for mechanical characterization. Prior to testing, samples are conditioned using an incubation system to 37 degrees Celsius and 90% relative humidity, mimicking in-use conditions of the reed. Initial microstructure analysis of each specimen is completed using optical microscopy to quantify fiber spatial arrangement, size and the existence of micro-cracks along the fiber-matrix interface. X-ray diffraction is also used to quantify the fraction of crystalline cellulose present in each sample. Specimens are then excited over a specific frequency range similar to that of in-use reeds using pressure waves in a non-contact setup. Values of internal friction are obtained as logarithmic decrement values for frequency-dependent decay. One set of specimens is then subjected to cyclic mechanical loading at low frequency (< 1Hz) and stresses up to 15MPa. The other set is maintained at the given environmental conditions using the incubator and aged through temperature and humidity cycling. Comparisons of post-testing microstructure damage and internal friction measurements are then completed to delineate specific degradation mechanisms due to mechanical/fatigue deterioration and moisture cycling. Internal friction is found to be dependent on both frequency, moisture and cyclic loading. Furthermore, the existence of microstructural cracks contributes to increasing decrement values at high frequencies in both fatigued and moisture cycled samples. Statistically significant correlations are discovered between logarithmic decrement and vascular bundle orientation at 700 Hz and logarithmic decrement and parenchyma cell diameter at 1000 Hz. Reductions in internal friction below 400 Hz indicate a decreasing loss modulus (E'') with increased moisture cycles, although this trend will be tested against a larger sample set in further work.